The Use of ADSCs as a Treatment for Chronic Stroke. Issue 4 (May 2014) - Chan, Tzu-Min; Harn, Horng-Jyh; Lin, Hui-Ping; Chiu, Shao-Chih; Lin, Po-Cheng; Wang, Hsin-I; Ho, Li-Ing; Chuu, Chih-Pin; Chiou, Tzyy-Wen; Hsieh, An-Cheng; Chen, Yu-Wen; Ho, Wen-Yu; et al.
Stroke is one of the disorders for which clinically effective therapeutic modalities are most needed, and numerous ways have been explored to attempt to investigate their feasibilities. However, ischemic- or hemorrhagicinduced inflammatory neuron death causes irreversible injuries and infarction regions, and there are currently no truly effective drugs available as therapy. It is therefore urgent to be able to provide a fundamental treatment method to regenerate neuronal brain cells, and therefore, the use of stem cells for curing chronic stroke could be a major breakthrough development. In this review, we describe the features and classification of stroke and focus on the benefits of adipose tissue-derived stem cells and their applications in stroke animal models. The results show that cell-based therapies have resulted in significant improvements in neuronal behaviors and functions through different molecular mechanisms, and no safety problems have so far arisen after transplantation. Further, we propose a clinical possibility to create a homing niche by reducing the degree of invasive intracerebroventricular transplantation and combining it with continuous intravenous administration to achieve a complete cure.